![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Đặt \(3x-1=y,x+2=z\)
\(\Rightarrow y^2-2yz+z^2=\left(y-z\right)^2\)
\(=\left(3x-1-x-2\right)^2=\left(2x-3\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-1\right)^3+4\left(x+1\right)\left(1-x\right)+3\left(x-1\right)\left(x^2+x+1\right).\)
\(=\left(x-1\right)^3+4\left(x+1\right)\left(1-x\right)+3\left(x-1\right)^3.\)
\(=\left(x-1\right)^3+4\left(1-x^2\right)+3\left(x-1\right)^3.\)
\(=\left(x-1\right)^3+3\left(x-1\right)^3+4\left(1-x^2\right)\)
\(=4\left(x-1\right)^3+4\left(1-x^2\right)\)
\(=4\left[\left(x-1\right)^3+\left(1-x^2\right)\right]\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(y+1\right)^4+\left(y-1\right)^4=\left(y+1\right)^4+\left[\left(y-1\right)^2\right]^2=\left(y+1\right)^4+\left[\left(y+1\right)\left(y-1\right)\right]^2=\left(y+1\right)^2\left[\left(y+1\right)^2+\left(y-1\right)^2\right]=2\left(y+1\right)^2\left(y^2+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1272 + 146.127 + 732
= 1272 + 2 . 73 .127 + 732
= (127 + 73 ) 2
= 200 2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x\left(x^2-16\right)-\left(x^2+1\right)\left(x-1\right)\) =\(x^3-16x^2-x^3+x^2-x+1\)
= \(x^2-17x+1\)
b) \(\left(y^2-9\right)\left(y^2+9\right)-\left(y^4-4\right)\) = \(\left(y^4-81\right)-\left(y^4-16\right)\)
=\(-65\)
CÁC BẠN KO CẦN GIẢI NỮA ĐÂU MÌNH BIẾT RỒI